A new species of Macrophya Dahlbom (Hymenoptera: Tenthredinidae) with a key to species of the Macrophya coxalis group from China. Issue 2 (28th January 2019) - Li, Ze‐Jian; Liu, Meng‐Meng; Wei, Mei‐Cai
Abstract: A new species, Macrophyra pseudocoxalis Li, Liu & Wei, sp. nov., of the genus Macrophya Dahlbom (Hymenptera: Tenthredinidae) from China is described. A key to known Chinese species of the Macrophya coxalis group is provided. The type specimens of the new species are deposited in the Lishui Academy of Forestry, Lishui, Zhejiang, China.